Die Stiftung von Autorschaft in der neulateinischen Literatur (ca. 1350-ca. 1650) Zur autorisierenden und wissensvermittelnden Funktion von Widmungen, Vorworttexten, Autorporträts und Dedikationsbildern - Enenkel, Karl A.E (Mittellateinische Studien und Texte, 2014)
This monograph throws new light on the question of authorship in the Latin literature of the early modern period. It shows that authorship was not something to be taken for granted in an empathic sense, but was chiefly to be found in the paratextual features of works - the dedication, preface, author's portrait and so on.; Readership: All interested in the history of literature, questions regarding authorship and readership, paratexts, literary practices and rituals (such as dedications), book history, sociology of literature, history of scholarship and science, and the transmission of knowledge.